A Sacred Marriage. Hierogamy in the Most Hermetic Art, from Alchemy to The Sacrifice, by Andrei Tarkovsky - Ferrer Ventosa, Roger (Eikón / Imago, 2022)
Many cosmogonies see the creation as a hierogamy, a non-dualist cosmogonic mytheme. It can also be found in alchemical engraving books, used in reference to one of the stages of the process, represented in iconography. In that phase, a woman and a man have sexual intercourse, like in the Rosarium Philosophorum. This iconographic type portrays a non-dual worldview, according to which the world needs to link both primary poles. This is achieved with resources inherent to visual art. Alchemy stands out as one of the few currents with a strong non-dual factor in Western schools. Subsequent artists were influenced by this iconography and the ideas represented in it, such as William Blake and surrealists like Leonora Carrington. It is also relevant as one of the most predominant motifs in the style of Andrei Tarkovsky, omnipresent in his work. It is in his last film, The Sacrifice, in which the alchemical universe is most present. In this film, the world is threatened by an apocalyptic Third World War, but a sexual ritual perhaps might reverse the crisis.